2018
DOI: 10.1002/jcp.27459
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor 3 agonist poly I:C reinforces the potency of cytotoxic chemotherapy via the TLR3‐UNC93B1‐IFN‐β signaling axis in paclitaxel‐resistant colon cancer

Abstract: Type I interferon (IFN) signaling in neoplastic cells has a chemo-sensitizing effect in cancer therapy. Toll-like receptor 3 (TLR3) activation promotes IFN-β production, which induces apoptosis and impairs proliferation in some cancer cells. Herein, we tested whether the TLR3 agonist polyinosinic: polycytidylic acid (poly I:C) can improve chemotherapeutic efficacy in paclitaxel (PTX) resistant cell lines. Human colon cancer cell lines HCT116, SW620, HCT-8 (sensitive to PTX), and HCT-8/PTX (resistant to PTX) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…It is presumed that NOVA2 worked for the metastasis of non-small-cell lung cancer (NSCLC) [ 75 ], colorectal cancer [ 76 ], and ovarian tumor [ 77 ] since its overexpression in these three cases. As an endosomal pattern-recognition receptor, TLR3 mediates innate immune response [ 78 ] and is found to induce apoptosis and thus result in oncogenesis, for instance, prostate cancer [ 79 ], non-small-cell lung cancer (NSCLC), breast cancer [ 80 ], colon cancer [ 81 ], papillary thyroid cancer [ 82 ], and nasopharyngeal carcinoma [ 83 ] as well as head and neck cancer [ 84 ]. By promoting oxidative phosphorylation and mitochondrial biogenesis, the activated PPARGC1A might accelerate metastasis [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is presumed that NOVA2 worked for the metastasis of non-small-cell lung cancer (NSCLC) [ 75 ], colorectal cancer [ 76 ], and ovarian tumor [ 77 ] since its overexpression in these three cases. As an endosomal pattern-recognition receptor, TLR3 mediates innate immune response [ 78 ] and is found to induce apoptosis and thus result in oncogenesis, for instance, prostate cancer [ 79 ], non-small-cell lung cancer (NSCLC), breast cancer [ 80 ], colon cancer [ 81 ], papillary thyroid cancer [ 82 ], and nasopharyngeal carcinoma [ 83 ] as well as head and neck cancer [ 84 ]. By promoting oxidative phosphorylation and mitochondrial biogenesis, the activated PPARGC1A might accelerate metastasis [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Natural products and their active derivates, including semi-synthetic and synthetic analogs, comprise one of the most important sources of chemotherapy drugs. Several plant-derived compounds, such as paclitaxel, vincristine, camptothecin and etoposide, have already been used against cancer for several decades (3)(4)(5)(6). Evodiamine (Evo), a quinolone alkaloid extracted from traditional herbal medicine Evodia rutaecarpa (7), has multiple pharmacological actions and could be used for obesity, inflammation, infectious and cardiovascular diseases (8).…”
Section: Introductionmentioning
confidence: 99%
“…[118][119][120] In line with these observations, Kline et al have recently demonstrated that intraperitoneal injection of polyI:C elicits robust anti-leukemia T cell immunity and considerably prolongs survival of leukemia-bearing mice upon the engagement of CD8α + cDC1s. 121 Several combinatorial regimens have been developed to increase the antineoplastic effects of polyI:C, some of which demonstrated pronounced therapeutic activity in preclinical models of melanoma 122,123 as well as CRC, 124,125 mammary, 124 and squamous carcinoma. 122 In particular, systemic administration of the DC growth factor fms-related receptor tyrosine kinase 3 ligand (FLT3 LG) followed by intratumoral polyI:C injections improved magnitude and duration of response to B-Raf protooncogene, serine/threonine kinase (BRAF) and CD274 (best known as PD-L1) blockade in mouse B16 melanomas, via a mechanism involving cDC1s.…”
Section: Preclinical Advancesmentioning
confidence: 99%
“… 122 Along similar lines, polyI:C and the microtubular poison paclitaxel 128 have been reported to synergistically inhibit the growth of paclitaxel-resistant human CRC cells in vitro through a pathway that involves enhanced interferon beta 1 (IFNB1) expression downstream of TLR3. 125 These latter findings suggest that the ability of polyI:C (and potentially other TLR3 agonists) to activate innate immune pathways in malignant cells may contribute to its therapeutic efficacy, 129 which is generally attributed to the engagement of the host immune system. Further supporting this possibility, TLR3 is known to promote apoptosis 98 , 130 , 131 as well as a non-apoptotic form of cancer cell death known as necroptosis, 132 134 which (at least in some settings) has therapeutic value.…”
Section: Preclinical Advancesmentioning
confidence: 99%